2015
DOI: 10.1212/wnl.0000000000001282
|View full text |Cite
|
Sign up to set email alerts
|

Placebo effect of medication cost in Parkinson disease

Abstract: This study provides Class III evidence that perception of cost is capable of influencing motor function and brain activation in Parkinson disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(92 citation statements)
references
References 34 publications
1
88
0
3
Order By: Relevance
“…While studies have reported a significant placebo response in adult patients (such as those with Parkinson's Disease [293]), placebo response rates are particularly high among children and adolescents in a subset of disorders, including psychiatric (anxiety, major depression, and obsessive compulsive and attention deficit disorders), medical (asthma), and painful (migraine, gastrointestinal) conditions [294,295]. As the current RCTs of CBD primarily target children with severe epilepsy, this may be an important issue.…”
Section: Placebo Effectmentioning
confidence: 99%
“…While studies have reported a significant placebo response in adult patients (such as those with Parkinson's Disease [293]), placebo response rates are particularly high among children and adolescents in a subset of disorders, including psychiatric (anxiety, major depression, and obsessive compulsive and attention deficit disorders), medical (asthma), and painful (migraine, gastrointestinal) conditions [294,295]. As the current RCTs of CBD primarily target children with severe epilepsy, this may be an important issue.…”
Section: Placebo Effectmentioning
confidence: 99%
“…Both of the "placebo cost" studies 5,6 found that placebo was more effective when its stated cost was higher. Perhaps greater expectations, generated by higher costs, mediate a greater placebo response.…”
Section: Critical Appraisal and Clinical Importancementioning
confidence: 99%
“…7 Some points, however, merit consideration. The most important point is that both of the "placebo cost" studies reviewed 5,6 were single-dose studies. There is no evidence to suggest that treatment cost will continue to influence treatment outcomes across weeks, months, or years of treatment, as is necessary in most psychiatric conditions.…”
Section: Clinical Pointsmentioning
confidence: 99%
See 2 more Smart Citations